2019
DOI: 10.1111/aec.12702
|View full text |Cite
|
Sign up to set email alerts
|

The response of cerambycid beetles (Coleoptera: Cerambycidae) to long‐term fire frequency regimes in subtropical eucalypt forest

Abstract: Fire has a varied influence on plant and animal species through direct (e.g. fire-induced mortality) and indirect (e.g. modification of habitat) effects. Our understanding of the influence of fire regime on invertebrates and their response to fire-induced modifications to habitat is poor. We aimed to determine the response of a beetle family (Coleoptera: Cerambycidae) to varying fire treatments and hypothesised that the abundance of cerambycid beetles is influenced by fire frequency due to modifications in hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…This is important to know because unplanned fires usually burn at a higher intensity and occur during drier conditions than planned fires, and differences in fire intensity may have significant ecological ramifications, resulting is modifications to an ecosystem (e.g. influencing plant regeneration) (Gosper et al 2013;Chick et al 2018;Eliott et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is important to know because unplanned fires usually burn at a higher intensity and occur during drier conditions than planned fires, and differences in fire intensity may have significant ecological ramifications, resulting is modifications to an ecosystem (e.g. influencing plant regeneration) (Gosper et al 2013;Chick et al 2018;Eliott et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the services that the insects provides, such as pollination, decomposition, and biological control of pests (Ramos et al 2020), cerambycid beetles have been negatively affected by deforestation caused by timber extraction and agricultural activity (IUCN 2019). A study conducted in Australia showed that the Cerambycidae community is influenced by burning regimes, which promote habitat alteration; the study showed that burned areas had a greater richness of beetles than unburned areas, and that the abundance of beetles in areas burned triennially was greater than that in unburned areas (Eliott et al 2019). The Cerrado is a biome closely linked to fire, and if the Cerambycidae community in Central Brazil follows the pattern found in Australia, it should also be affected by this factor.…”
Section: Introductionmentioning
confidence: 99%
“…Forests are important habitats for longhorn beetles. Forest composition, forest management, forest re, environmental change, and spatial heterogeneity all affect the distribution of longhorn beetle diversity (Toledo et al 2002;Ohsawa 2004;Eliott et al 2019). Stand type, stand age, composition, sectional area, diameter at breast height (DBH), and dead wood affect the richness and abundance of longhorn beetles (Grove 2002 (Luo et al 2021).…”
Section: Introductionmentioning
confidence: 99%